Narasi Kekerasan Seksual Terhadap Perempuan dalam Lembaran Kitab Kuning - Syamsuri, Syamsuri; Syafaat, Abdul Kholiq; Ghufron, Muhammad; Khazin, A. Mufti (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
This article reviews sexual violence against women found in the narrative of the yellow book, especially in the context of Islamic law and customs. Although Islam emphasizes the safety, peace, and respect for women, there is an ambiguity in the meaning of the holy text that can trigger interpretations that support violence. This is exacerbated by some scholars who have conservative views on the role of women, which are then immortalized in the yellow book. This article also highlights that violence against women is often supported by biased interpretations of the verses of the Qur'an and hadith. In conclusion, the yellow book, as a reference for Islamic teachings in Islamic boarding schools, needs to be reviewed to eliminate the narrative of violence and ensure respect for women in accordance with the true teachings of Islam.